Does wind speed and direction influence timing and route of a trans-hemispheric migratory songbird (purple martin) at a migration barrier? - Abdulle S. A. (De Gruyter, 2018)
The influence of weather on the departure decisions and routes of migratory birds can now be further investigated with the use of direct tracking methods. We tested hypotheses for migration departure decisions and flight trajectories by determining the influence of wind speed and direction at the Yucatan peninsula in spring on departure date, migratory route, and longitude of arrival at the northern Gulf coast of a trans-hemispheric migratory songbird, purple martin (Progne subis). Birds were equipped with geolocators at their breeding colony and 36 were recaptured upon return after spring migration. While southerly tailwinds with low wind speeds prevailed at the Yucatan during the period of passage, we found that daily wind speed and direction were still important predictors of departure date. However, wind conditions at departure did not predict longitude of arrival at the US gulf coast after crossing the gulf. Birds appeared to favour the shortest distance across the Gulf of Mexico, aided by consistent tailwinds, but may have corrected for wind drift so as to land at a longitude near 88°, reflecting the shortest distance across from the Yucatan staging areas. Considering their use prior to departure, high quality roost sites at the Yucatan peninsula would be important conservation targets for this declining aerial insectivore.